Frog goes to dinner - Mayer, Mercer, 1943- (New York : Dial Books for Young Readers, 1974)
Having stowed away in a pocket, Frog wreaks havoc and creates disgrace for the family at the posh restaurant where they are having dinner.
Keywords: Frogs -- Fiction; Stories without words